'Extended Arm of Reich Foreign Policy'? Literary Internationalism, Cultural Diplomacy and the First German PEN Club in the Weimar Republic. (May 2021) - Windsor, Tara Talwar
Abstract : This article examines the first German PEN Club (established in 1924) as a semi-formal agent of cultural diplomacy after the First World War. It shows that leading figures in the German PEN negotiated a role in the International PEN which blended PEN's ostensibly non-political literary internationalism with the national interests of the young Weimar Republic. It explores their mutually expedient relationship with the German Foreign Ministry their efforts to influence state cultural diplomacy and their use of the International PEN framework to test alternative visions of international order. The article complicates the notion that PEN was an 'instrument' or 'extended arm' of foreign policy by underlining the agency of PEN intellectuals and by showing how PEN was part of a wider search for new ways to shape international affairs and find ideological compromise in an era often seen through a dominant lens of confrontation and polarisation.